2016
DOI: 10.1055/s-0036-1586376
|View full text |Cite
|
Sign up to set email alerts
|

Serum leptin levels among malnourished children with and without pneumonia

Abstract: The aim was to evaluate the serum leptin level in children with protein-energy malnutrition (PEM) with and without pneumonia. The study included 60 children; 20 were controls, 20 had PEM without infection and 20 had PEM and pneumonia. They were subjected to nutritional assessments; serum leptin level, haemoglobin concentration, white-blood cell (WBC) count, CD4%, serum albumin, blood glucose, blood urea-nitrogen, and serum ferritin, and chest x-ray. Serum leptin levels were independently associated with pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…On the other hand, Al Biltagi et al found that low serum leptin level was associated with pneumonia in Table 3 Comparison of serum leptin between different grades of pneumonia severity malnourished children [16]. This may be attributed to lower serum leptin in malnourished children than in healthy controls [17,18].…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, Al Biltagi et al found that low serum leptin level was associated with pneumonia in Table 3 Comparison of serum leptin between different grades of pneumonia severity malnourished children [16]. This may be attributed to lower serum leptin in malnourished children than in healthy controls [17,18].…”
Section: Discussionmentioning
confidence: 98%